Green Building Adoption in Malaysia: Multiple Case Studies Approach - Lee, Randy Eng Wei (2016)
With the ever-growing concern in global warming and amid the nature resources being depleted at an alarming rate, there have been a proliferation focus on the impact of construction industry towards environment. Therefore, the purpose of this study is to explore on the willingness and challenges faced by the developers in green building adoption in Malaysia. In Malaysia, the adoption of green building is still at low level and at its infancy stage, therefore this study will provide a better insight of the challenges faced and reduce the gap in literature in this area of study. This research will adopt the qualitative case study approach using a multiple case studies design. The data will be collected through interview of directors and project manager of a public listed developer company and a SME company. The data collected will then be analysed and compared to provide a comprehensive finding of similarities and differences between both organisations in terms of the challenges and willingness in green building adoption. The data has been collected from 5 interviewees and the data is texted in transcript and cleared for proposition testing. Form the findings, the awareness level among the developers are high and they are very much willing to adopt green building in the future project. Involvement and encouragement from stakeholders show little sign of persuasion for developers to adopt green building since it cannotes to cost. Hence, cost will still be the deterrent factor in embracing green building nevertheless, through the encouragement and involvement from government, the developer will be more susceptible to adopt green building. In conclusion, green building is not an emerging trend or luxury but rather an obligation for the construction industry players to embrace it for the better and sustainability of the future generation though traversing ahead will bound to encounter many challenges. Challenges are inevitable and crucial part of any successful journey.